The Peat Soil of Sarawak : Existing Knowledge and Information Gaps - Wee, Boon Siong; Murtedza, Mohamed; Padmanabhan, Eswaran; Mei, B. L. H. (Universiti Malaysia Sarawak (UNIMAS), 2020)
Peat in strict definition usually refers to the accumulation of a purely one hundred percent organic material and the distinction between soil and vegetative accumulation is not clear (Andriesse,1992). Over the years, ‘peat’ has been alternately referred to as ‘organic soils’ and Histosols. Tie (1979) refers to peat as organic soils on the basis of mass composition i.e. soils that contain at least 65% organic matter or conversely, less than 35% mineral content. The more recent definition for organic soils as adopted by the Soil Division of Sarawak is based on profile partition, i.e. soils that have 50 cm or more organic soil matter within 100 cm or more than twice that of mineral soil materials overlying bedrock within 50 cm (Teng, 1996). On the other hand, USDA defines a soil type as organic soils (or Histosols) if more than half of the upper 80 cm of the soil is organic or if organic soil material of any thickness rests on rock or on fragmental material having interstices filled with organic materials (Soil Survey Staff, 1998).